Evaluating the Degree of Readiness to Practice Professional Distance Learning Communities (Virtually) in Light of the Covid-19 Crisis: Perspectives of School Leaders and Teachers at Amman Educational Directorate in Jordan - Nofal , Mohammad Baker; Abu Khalifeh, Ibtisam Tawfiq; Rommaneh, Abeer Khalil (Dirasat: Educational Sciences, 2023)
Objective: This study aims to evaluate the degree of readiness to practice virtual PLCs in light of the COVID-19 crisis from the perspectives of school leaders and teachers at Amman Educational Directorate in Jordan. Methods: This study used the descriptive analytical method. The sample of the study consisted of 155 respondents chosen randomly. The psychometric properties of the Professional Learning Communities Scale, consisting of 52 items distributed across six dimensions, were validated. Results: The results showed that the degree of readiness to practice virtual PLCs in light of the COVID-19 crisis, from the perspectives of school leaders and teachers, was high across all dimensions of the scale. Specifically, Supportive Conditions – Relationships were ranked first with a high score, while Supportive Conditions – Structures were ranked second with a medium score. The Shared Values and Visions, Shared Personal Practices, and Shared and Supportive Leadership were ranked third, fourth, and fifth, respectively, with a medium score. The results indicated significant statistical differences in work type and authority supervising schools, in favor of school principals and UNRWA schools, respectively. However, there were insignificant statistical differences regarding the respondents' gender, years of experience, and academic degrees. Conclusions: The results demonstrate that the degree of readiness to practice virtual PLCs in the light of the COVID-19 crisis, from the perspectives of school leaders and teachers, was high. The study recommends conducting related studies and holding workshops for school leaders and teachers.